THE USE OF SMARTPHONES AS EXTRAMURAL ENGLISH LEARNING TO ENRICH EFL LEARNERS’ VOCABULARY - Daning Hentasmaka; Rosi Anjarwati; Afi Ni'amah (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2022)
Smartphone has long been considered as a double-edged sword which has both positive and negative effects.  Instead of banning the use of smartphones, a smart teacher has to be able to encourage EFL learners to use smartphones wisely to facilitate their learning. Smartphones enable the learners to use the language in a real situation outside the classroom, which is called Extramural English Learning. This kind of situation is believed to contribute to learners vocabularies. Learners’ ability to use various kinds of vocabulary, especially English academic words, will make a positive contribution to their writing. Employing a correlation design, the aim of the research was to investigate the correlation between the use of smartphones as extramural English learning and learners’ vocabularies focusing on English academic words. Questionnaire and writing test were used as instruments to collect the data from 35 undergraduate students of English department in East Java, Indonesia. The results of the data analysis by using Pearson Correlation confirmed the significant positive correlation between the use of smartphones as extramural English learning and learners’ vocabularies that indicated the benefit of extramural activities with smartphones on enriching learners’ vocabulary. Further, the pedagogical implication was also discussed.